2020
DOI: 10.1002/celc.201902050
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Capacity Degradation Mechanism of Li‐ion Battery in Fast‐charging Process

Abstract: In this work, capacity degradation in fast-charging process is studied by using a power-optimized graphite-Li-Ni 0.80 Co 0.15 Al 0.05 O 2 (NCA) electrode couple and a three-electrode coin cell as the testing vehicle. It is shown that capacity degradation consists of two distinct stages, (1) rapid degradation in early period and (2) progressive degradation over lifetime, which are associated with the electrochemical reduction of electrolyte solvents on the graphite anode and the structural deterioration of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 29 publications
2
40
0
Order By: Relevance
“…Although Li plating has been overwhelmingly considered the culprit of fast charge problems, it was found that even if the potential of the graphite anode never drops below 0 V vs. Li/Li + during 10 C‐charging in power‐optimized Gr/NCA cells, the accelerated performance degradation is still unavoidable. Similarly, Mussa et al reported that energy‐optimized batteries (25 Ah, Gr/NMC111) release large amounts of gas, accompanied by severe graphite exfoliation, as the batteries are charged at 4 C. The above results point to the fact that under fast charge, the existing SEI on the graphite anode is unable to protect electrolyte solvents from electrochemical reduction.…”
Section: Challenges and Strategiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Although Li plating has been overwhelmingly considered the culprit of fast charge problems, it was found that even if the potential of the graphite anode never drops below 0 V vs. Li/Li + during 10 C‐charging in power‐optimized Gr/NCA cells, the accelerated performance degradation is still unavoidable. Similarly, Mussa et al reported that energy‐optimized batteries (25 Ah, Gr/NMC111) release large amounts of gas, accompanied by severe graphite exfoliation, as the batteries are charged at 4 C. The above results point to the fact that under fast charge, the existing SEI on the graphite anode is unable to protect electrolyte solvents from electrochemical reduction.…”
Section: Challenges and Strategiesmentioning
confidence: 99%
“…Therefore, effective additives for the layered cathode are mainly centered on the compounds that can react with the alkaline Li residual compounds, such as sulfates & sultones, phosphates & phosphites, and borates . As pointed out in Section 3.1, electrolyte solvents are subject to electrochemical reduction on the graphite anode under fast charge . In this view, the electrolyte additives are of particular significance in mitigating capacity fade and stabilizing coulombic efficiency under fast charge.…”
Section: Challenges and Strategiesmentioning
confidence: 99%
See 3 more Smart Citations